The Effect of Angklung Musical Instrument on the Ability to Recognize Number Symbols and Fine Motorik of Children Aged 5-6 Years - Lia Indah Septiwin Widorini; Rachma Hasibuan; Retno Trihariastuti (International Journal of Trends in Mathematics Education Research, 2019)
This study aims to educate early childhood children about learning to recognize number notation easily and how to play angklung correctly. With the playing Angklung can develop the ability to recognize symbols of the numerical notation and fine motor that is coordinating between eyes by hand. This study was conducted in children aged 5-6 years at the Taman Kasih Kindergarten in Surabaya, with a total of 23 control classes and 23 experimental classes for children. This study uses quantitative research that uses experimental methods and has a control group. The feasibility of angklung media from media experts and material experts with very valid criteria and is appropriate to use. Pretest results of children's abilities are still many who have not developed 74%, have not developed 4%, and have developed as expected 17%. After being given treatment using the angklung instrument, the ability of 70% of children to develop is very good and 30% to develop as expected. Based on the data above, the angklung media used in playing musical instruments in recognizing numerical notation symbols can improve the cognitive aspects of early childhood development while the results of pretest results of fine motor skills of children are still at the stage of developing as much as 54% and fine motor skills that develop as expected as much as 46%. After being treated as much as five times, then held a posttest increased to fine motor skills of children to develop very well 76% and develop as expected 24%.